Drivers of benthic invertebrate diversity in the protected Walpole-Nornalup Estuary, southwest Australia - Leal, Inês; Rule, Michael J.; Lavery, Paul S.; Wilson, Shaun K. (Biodiversity and conservation, 2025)
A changing climate combined with increasing human development and pollution along riparian areas result in cumulative pressures that alter fauna distribution and diversity in estuaries. One of the very few southwest estuaries in Australia that supports high biological diversity is the protected Walpole-Nornalup Estuary. However, little is known of how fauna varies spatially and temporally in response to the local seasonal cycles, information that is essential to benchmark fauna condition and vulnerability. Accordingly, this study aimed to characterize the invertebrate assemblages among the main benthic habitats of varying sediment type in the inlets and discern the suite of environmental variables that drives their richness and abundance. Sampling was done seasonally from 2010 to 2012, with a total of 18,176 organisms from 77 species across 51 taxonomic families being recorded. Polychaete worms, malacostracans and bivalves comprised over 90% of the benthic invertebrate community. Polychaetes not only dominated in terms of abundance but were also the most diverse group with the highest family richness recorded (19 families). Sediment type was one of the greatest determinants of community composition, with more invertebrates and taxa found within sandy sediments at the oceanic opening and shallow peripheral banks of the estuary, compared to the inner muddy basins. Localized levels of pH, dissolved oxygen and salinity, along with broader climatic drivers, such as rainfall, influenced the abundance of specific families, including nereidid, spionid, orbiniid and opheliid worms, aorid amphipods and psammobiid bivalves. These results indicate that environmental change may affect the distribution patterns and diversity of invertebrate assemblages within this marine park and management approaches should consider the response of these sensitive macrobenthic fauna.